2015
DOI: 10.1073/pnas.1416622112
|View full text |Cite
|
Sign up to set email alerts
|

Crossovers are associated with mutation and biased gene conversion at recombination hotspots

Abstract: Meiosis is a potentially important source of germline mutations, as sites of meiotic recombination experience recurrent double-strand breaks (DSBs). However, evidence for a local mutagenic effect of recombination from population sequence data has been equivocal, likely because mutation is only one of several forces shaping sequence variation. By sequencing large numbers of single crossover molecules obtained from human sperm for two recombination hotspots, we find direct evidence that recombination is mutageni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
218
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(257 citation statements)
references
References 47 publications
(59 reference statements)
23
218
2
Order By: Relevance
“…Gene conversion is biased in favor of transmission of GC alleles in many eukaryotes (Duret and Galtier 2009). Such a bias has been observed directly in noncrossover (Odenthal-Hesse et al 2014) and crossover (Arbeithuber et al 2015) recombination products in human sperm and can explain patterns of GC content enrichment at mouse hot spots (Clement and Arndt 2013). Accordingly, we found that, in males, noncrossovers frequently showed significant bias, resulting in more conversion to GC than to AT (Supplemental Table S2).…”
Section: Biased Gene Conversion In Noncrossoversmentioning
confidence: 53%
“…Gene conversion is biased in favor of transmission of GC alleles in many eukaryotes (Duret and Galtier 2009). Such a bias has been observed directly in noncrossover (Odenthal-Hesse et al 2014) and crossover (Arbeithuber et al 2015) recombination products in human sperm and can explain patterns of GC content enrichment at mouse hot spots (Clement and Arndt 2013). Accordingly, we found that, in males, noncrossovers frequently showed significant bias, resulting in more conversion to GC than to AT (Supplemental Table S2).…”
Section: Biased Gene Conversion In Noncrossoversmentioning
confidence: 53%
“…Moreover, direct interaction between Rev1, Polz, and components of the DSB-forming machinery (Spo11, Mei4, Rec114) is suggested by yeast twohybrid interactions (Arbel-Eden et al 2013). Further support for a role of TLS polymerases in meiosis comes from the observation that Polz also makes a major contribution to the elevated mutation rate that is associated with meiotic recombination (Arbeithuber et al 2015;Rattray et al 2015). Recruitment of alternative DNA polymerases to damage sites is mediated by ubiquitylation of PCNA at K164 (Dieckman et al 2012).…”
Section: Recombination-associated Dna Synthesismentioning
confidence: 99%
“…Direct observations of gBGC have been first provided by the analysis of a few specific recombination hotspots (OdenthalHesse et al 2014;Arbeithuber et al 2015). Recently, Williams and colleagues published a large-scale study of gene conversion tracts associated with noncrossover (NCO) recombination events in humans (Williams et al 2015).…”
Section: Comparison With Direct Measures Of Gbgc In Noncrossoversmentioning
confidence: 99%